Mental Workload Analysis Using NASA TLX on Healthcare Workers in the Emergency Room of Sariningsih Hospital Class IV, Bandung City - Azmi, Bheta Silfana Ulul; Zulmansyah, Zulmansyah; Kesuma , Nirmala (Yayasan Gema Bina Nusantara, 2025)
Human resources (HR) are an integrated expertise that comes from the mental and physical power possessed by each individual and is something that is very important for the activities carried out. Emergency Room (IGD) is one of the most important work units in a hospital. The purpose of this study was to describe the Mental Demand (MD), Physical Demand (PD), Temporal Demand Frustration (FR), Effort (EF) and Performance (PE) of doctors, nurses and midwives in the Emergency Room of the Sariningsih Level IV Army Hospital, Bandung City. The research method used in this study was quantitative descriptive with a sample size of 39 health workers. Based on the research results obtained by the author, it is known that the majority of health workers in this study who experience a very high mental workload, namely doctors were found in the physical demand aspect with a total of 6 people and temporal demand was found with a total of 5 people. While for nurses, it was found in the mental demand aspect with a total of 9 people, performance with a total of 7 people, frustration with a total of 7 people, and effort with a total of 5 people. And for midwives, it was found in all aspects at a high level. So based on the total Nasa TLX score, the overall mental workload of health workers in the RST Level IV Emergency Room. IV 03.07.03 Sariningsih Bandung City is classified as moderate.